STUDI TENTANG MONUMEN PEMERINTAHAN DARURAT REPUBLIK INDONESIA DI KOTO TINGGI KABUPATEN LIMA PULUH KOTA - Dra. Ernis, M.Pd., WIMAS MULYABER, Dra. Lisa Wisdiarti, M.Sn., (Serupa The Journal of Art Education, 2016)
This struggling of monumental PDRI creation is one of identities to commemorate or remind the important event by a social group as a part of expotulation the struggle history of PDRI at Koto Tinggi, West Sumatera in the past. Now, the condition of munument is poor because there is no people try to keep it again, and most of the society do not know about the monument itself.This research is purposed for describing and analysing the monument building of PDRI from it structures until the meaning of its build.This research use the qualitative methodology with the sort of description research to describe everything that was found on the field, and it agrees with the research and reality. The purpose of descriptive method is to describe or analyze the result of research, but it does not use to make more widely conclusion.The result of research shows that PDRI monument was built for remembering the PDRI (The Emergency Government Monument Of Indonesian Republic) events. It is about the moving of central country, Jakarta, to West Sumatera. The factor that influence PDRI monuments are history factors, the person who was in the event, and designers. Meanwhile, the meaning of its become the core prinsipal on designing monument. Beside that, the monument is not just an evidence of event that it was happend, but it’s to be a characteristic and identity of a place. Thus, the monument has to be able to give an impression about history and a message for society.Keywords : PDRI Monuments, Structures and Meaning.